Economic Valuation of Parthenium Weed Control Measures, in Gurage Zone, SNNPR of Ethiopia (Global Journal of Science Frontier Research, 2018)
The study was initiated to estimate the monetary value that farmer households' are willing to pay for the control measure of Parthenium weed and to identify the factors determining their level of willingness to pay amount. The primary data were collected from 320 sample households drawn randomly from two purposively selected districts, Abeshige and Kebena (160 from each districts), in Gurage zone, SNNPR of Ethiopia. Both descriptive statistics and Tobit model were used to analyze the data. To elicit and estimate farmers' responses on the amount of willingness to pay for the control measures of Parthenium weed, a contingent valuation approach involving a single bound with open ended follow up format was used. Accordingly, the estimated mean WTP for the control measure of Parthenium weed was estimated to be 168.52birr per year per household. In addition, the total maximum willingness to pay (which consists of 6,742 households in all sampled kebeles from both districts) was estimated to be 795,313.288 birr per year. The Tobit model estimates revealed that age, education, livestock ownership, off/non-farm sources of income, past awareness, assistance and membership were found to be the most important determinant factors that affect households' maximum willingness to pay for the control measures of Parthenium weed in the study area.
Keywords: invasive alien plant species (IAPS); parthenium weed; economic valuation; contingent valuation method (CVM); gurage zone